Ca2+ signalling is critical for autoantibody‐induced blistering of human epidermis in pemphigus. (31st May 2021) - Schmitt, T.; Egu, D.T.; Walter, E.; Sigmund, A.M.; Eichkorn, R.; Yazdi, A.; Schmidt, E.; Sárdy, M.; Eming, R.; Goebeler, M.; Waschke, J.
Summary: Background: Pemphigus is a severe bullous autoimmune skin disease. Pemphigus foliaceus (PF) is characterized by antidesmoglein (Dsg) 1 IgG causing epidermal blistering; mucosal pemphigus vulgaris (mPV) by anti‐Dsg3 IgG inducing erosions in the mucosa; and mucocutaneous pemphigus vulgaris (PV) by affecting both, with autoantibodies targeting Dsg1 and Dsg3. Objectives: To characterize the Ca 2+ flux pathway and delineate its importance in pemphigus pathogenesis and clinical phenotypes caused by different antibody profiles. Methods: Immunoprecipitation, Ca 2+ flux analysis, Western blotting, immunofluorescence staining, dissociation assays and a human skin ex vivo model were used. Results: PV IgG and PF IgG, but neither Dsg3‐specific monoclonal antibody (AK23) nor mPV IgG, caused Ca 2+ influx in primary human keratinocytes. Phosphatidylinositol 4‐kinase α interacts with Dsg1 but not with Dsg3. Its downstream target – phospholipase‐C‐γ1 (PLC) – was activated by PV IgG and PF IgG but not AK23 or mPV IgG. PLC releases inositol 1, 4, 5‐trisphosphate (IP3) causing IP3 receptor (IP3R) activation and Ca 2+ flux from the endoplasmic reticulum into the cytosol, which stimulates Ca 2+ release‐activated channels (CRAC)‐mediated Ca 2+ influx. Inhibitors against PLC, IP3R and CRAC effectively blocked PV IgG and PF IgG‐induced Ca 2+ influx; ameliorated alterations of Dsg1 and Dsg3 localization, and reorganization of keratin and actin filaments; and inhibited loss of cell adhesion in vitro . Finally, inhibiting PLC or IP3R was protective against PV IgG‐induced blister formation and redistribution of Dsg1 and Dsg3 in human skin ex vivo . Conclusions: Ca 2+ ‐mediated signalling is important for epidermal blistering and dependent on the autoantibody profile, which indicates different roles for signalling complexes organized by Dsg1 and Dsg3. Interfering with PLC and Ca 2+ signalling may be a promising approach to treat epidermal manifestations of pemphigus. Abstract : What is already known about this topic? Autoantibody‐induced Ca 2+ signalling and activation of phospholipase C in keratinocytes has been reported as the first signalling pathway in pemphigus. Ca 2+ influx correlates with the presence of autoantibodies targeting desmoglein (Dsg) 1. The role and exact mechanisms of the Ca 2+ signalling pathway and its role in pemphigus pathology are unclear. What does this study add? There is an important role of the phospholipase C/Ca 2+ signalling pathway in the pathogenesis of pemphigus. Relevant signal components of the Ca 2+ pathway are characterized in detail. Dsg1 and Dsg3 are found to interact with signalling molecules, organizing signalling complexes that differ with respect to the presence of phosphatidylinositol 4‐kinase α, the most upstream activator of the Ca 2+ ‐influx pathway, assigning different roles to Dsg1‐ and Dsg3‐mediated signalling. What is the translational message? Current therapies for pemphigus have a delayed onset of action. Rapidly effective therapeutic approaches that directly stabilize desmosomal adhesion are desirable. While targeting the Ca 2+ flux is problematic, the role of phospholipase C in the influx identifies this molecule as a potential target for specific molecular therapy approaches. Elucidating the mechanism of Dsg1‐dependent regulation of Ca 2+ influx in keratinocytes helps us to understand the different blistering patterns and the phenotypic variability seen in pemphigus. Plain language summary available online